IRAIT: a Telescope for Infrared Astronomy from Antarctica - TOSTI, Gino; BUSSO, Maurizio Maria; S. Ciprini; P. Persi; M. Ferrari Toniolo; L. Corcione (2003)
We present the status of the project IRAIT (the Italian Robotic Antarctic Infrared Telescope), that will be hosted at Dome C in the Italo-French Concordia station on the Antarctic Plateau. We review the main scientific motivations of the effort, and describe the main characteristics of the telecope, which has been completed and is now under test at the Coloti-Montone site, operated by the University of Perugia, and its focal plane instrumentation.